An In-Vitro Study to Investigate anti-inflammatory and thrombolytic activity of methanolic extract of blumea lacera leaves - Tahsin, Faria (Brac University, 2020)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2019.